2018
DOI: 10.21743/pjaec/2018.06.06
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of K+, Na+and Cl-Content in Rice Tissues and Soil Irrigated With Wastewater

Abstract: In recent years, many studies have been devoted to investigating consequence of wastewater usage in irrigation. Herein, assessment of wastewater irrigated rice crop (selected rice cultivars such as, Shandar, Shua-92 and Sarshar) irrigated water and cultivating soil samples of Tandojam, Hyderabad city and its vicinity were selected for analysis. In this study, pH, EC, Na + , K + and Clions were observed for wastewater, irrigated rice cultivars and soil, and compared with canal water irrigated rice cultivars and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…De acuerdo con la clasificación del agua de riego por salinidad (Ayers y Westcot 1985), el 5.7 % de las muestras no presenta ninguna restricción, el 85.7 % presenta riesgo de ligero a moderado y el 8.6 % presenta grado de restricción severo para el riego agrícola. Los sitios con mayor CE fueron el río Tula y una serie de 10 sitios muestreados entre la autopista Peñón-Texcoco y el Las aguas residuales municipales e industriales por lo general tienen altas concentraciones de iones que pueden formar las sales NaCl y NaHCO 3 por los desechos de restaurantes, hospitales e industrias, entre otros (Soothar et al 2018). Aunque éstas no son las únicas sales que podrían formarse, por lo general se encuentran en mayor cantidad.…”
Section: Salinidadunclassified
“…De acuerdo con la clasificación del agua de riego por salinidad (Ayers y Westcot 1985), el 5.7 % de las muestras no presenta ninguna restricción, el 85.7 % presenta riesgo de ligero a moderado y el 8.6 % presenta grado de restricción severo para el riego agrícola. Los sitios con mayor CE fueron el río Tula y una serie de 10 sitios muestreados entre la autopista Peñón-Texcoco y el Las aguas residuales municipales e industriales por lo general tienen altas concentraciones de iones que pueden formar las sales NaCl y NaHCO 3 por los desechos de restaurantes, hospitales e industrias, entre otros (Soothar et al 2018). Aunque éstas no son las únicas sales que podrían formarse, por lo general se encuentran en mayor cantidad.…”
Section: Salinidadunclassified
“…On the other hand, Sandri et al (2009) reported that after two cultivation cycles of Elisa lettuce, TSE irrigation promoted higher levels of potassium, manganese, copper, sulfur and electrical conductivity, but there was no observed difference in CEC, organic matter, magnesium, calcium, total nitrogen, sodium and phosphorus when compared to dam water. Sandri and Rosa (2017), when irrigating banana trees with surface drip irrigation and micro sprinkler using treated sewage effluent (Ie), conventional fertigation and well water, observed that the levels of Na and B declined or remained stable in the soil, but drip application of the effluent raises the levels of phosphorus, sulfur, total acidity and base saturation in the soil layer from 0 to 0.2 m and when using the micro sprinkler in the layer of 0.2 to 0.4 m. Soothar et al (2018) concluded that the use of untreated sewage had unacceptable levels of EC, pH, K + , Na + and Cl -, which resulted in excessive concentrations of these ions in both rice plant (Oryza sativa) and irrigated soil. In view of the conclusion of these authors, it is verified that the type of sewage treatment can be a differential, thus, the use of SZR can be an alternative in the sense of assisting in the previous removal of part of the fertilizers present in the effluent.…”
Section: Chemical Attributes Of the Soilmentioning
confidence: 99%
“…14 n. 5, e2341 - Taubaté 2019 2017 agricultural production due to its great potential to provide nutrients to the plants, helping to promote sustainable agriculture and rural development. According to Monteiro et al (2014), Lavrnié et al (2017), Soothar et al (2018) and Papaioannou et al (2018), wastewater has been widely used as fertigation due to its contribution of nutrients that benefit the development of crops, its potential to improve the soil chemical properties, and because it effectively contributes to environmental protection, in addition to being a viable alternative for controlling water demand in regions with low availability of water resources. In addition, it increases crop yields and farmer profit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater irrigation affects plants and soil due to the presence of heavy metals elements pollution in most of it [5]. Accordingly, it is extremely important to obtain efficient methods to remove heavy metals from polluted water.…”
Section: Introductionmentioning
confidence: 99%